Forensic evaluation of craniometric characteristics of the Kazakhstan population - Saule A. Mussabekova; Anastasiya O. Stoyan; Xeniya E. Mkhitaryan; Saule B. Zhautikova (Journal of Oral Biology and Craniofacial Research)
Background: The human skull is the part of the skeleton most frequently used in population studies, as it was more exposed to genetic factors and less exposed to environmental factors. The skull is an important component in human forensic identification. Materials and methods: The craniometric characteristics of 186 male and 114 female skulls found on the territory of Kazakhstan were studied. Dimensions were measured using standard anthropometric methods and instruments. The results of measurements of 25 craniometric parameters are presented. Methods of descriptive and parametric statistics were used. Results: Statistical analysis showed significant regional dimorphism, confirming theindividuality of the Kazakhstan population. Statistically significant deviations werefound in 6 male craniometric characteristics and 4 female craniometric characteristics(p<0.05). The most dimorphous variables for regional identification in Kazakhstanmales were the higher skull base and frontal chord width , full face height , condylarand bigonial width , and low mandibular body reference values (p<0.05). For females,significant statistical discrepancies were seen in the transverse diameter and skullbase width, mastoid and occipital aperture width (p<0.05). Conclusion: The recorded variations and changes in the morphology of the humanskull of the population of Kazakhstan indicate the need to develop and updateosteometric standards used in practice for specific populations. All this will significantlyimprove the accuracy of forensic identification and more fully study the biologicalpatterns of population formation, as well as evaluate the comparative effectiveness ofindividual features in the reconstruction of the population history of various populationgroups.